Mass Transfer Coefficient of Extraction of Anthocyanin from Mangosteen Peel (Garcinia mangostana L.) with Ethanol-HCl as Solvent - Zubaidi Achmad; Faizah Hadi; Siti Diyar Kholisoh (Eksergi, 2022)
Anthocyanin is a natural pigment that causes the purple skin of the mangosteen fruit. This study aimed to observe the effect of temperature, stirring time, and ethanol concentration in ethanol–HCl solvent on anthocyanins produced from the mangosteen peel extraction process and determine the value of its mass transfer coefficient. The laboratory work was conducted with mangosteen peel powder extracted with ethanol solvent containing 1% HCl solution using an extraction apparatus set. The mangosteen rind is cleaned and then mashed until it passes the size of -60+80 mesh. Then 50 g of mangosteen rind powder was put into a three-neck flask along with ethanol solution with various concentrations of 55%, 65%, 75%, 85%, and 95%, each containing 1% HCl. Extraction was carried out at various stirring times of 3, 4, 5, 6, and 7 hours with temperature variations of 30, 40, 50, 60, and 70oC. Each product was distilled at a temperature of <60oC. Anthocyanin content were analyzed by spectrophotometric method. The results showed that the optimum conditions at the extraction temperature of 50oC with stirring time for 4 hours and 95% ethanol concentration in ethanol–HCl solvent with anthocyanin content obtained of 9,8377.10-4 (g anthocyanin/g solvent) and kC of 0,00781 g/(cm2.hour).